Analisis Store Atmosphere dan Sales Promotion terhadap Impulse Buying yang Dimediasi oleh Shopping Emotion pada Toko Ritel Modern Miniso di Kota Bandung - Amanda Risma Nurafifah; Desmiza Desmiza (Journal of Management and Bussines (JOMB), 2024)
This research aims to analyze the influence of store atmosphere and sales promotion on impulse buying mediated by shopping emotion at the Miniso modern retail store in Bandung City. Quantitative approach method using surveys based on deductive reasoning. The sample collection technique used was purposive sampling. Data was obtained from a survey distributed online using a Likert scale questionnaire with cross-sectional or shot study data collection techniques. The research results show that store atmosphere and sales promotion have a positive effect on impulse buying directly. However, store atmosphere and sales promotion have no effect on impulse buying through shopping emotion. In conclusion, although store atmosphere and sales promotion have a direct influence on impulse buying, they do not influence shopping emotion. This shows that other factors may be more dominant in mediating the relationship between store atmosphere and sales promotion and impulse buying. Keywords: Store Atmosphere, Shopping Emotions, Impulsive Buying, Sales Promotion